A study on the association of diabetes and semen quality in and around Chennai, Tamil Nadu, India - S., Kalaiselvi; Ali M., Syed; V., Anuradha; A., Subhashini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Globally prevalence of diabetes is gradually increasing in individual at reproductive stage. Uncontrolled blood sugar affects biological systems including reproductive. Thus, this study was aimed to analyze the association of diabetes and male infertility in and around Chennai. Methods: Fifty-four male participants who visited the fertility clinic was grouped in two based on the sugar value. An anthropometric measurement, clinical, blood, seminal parameters and life style behaviors was analyzed. All study variables was analyzed to examine the association of diabetes and semen quality. Results: Study results shows that people with diabetes had abnormal semen parameters as compared to non- diabetic study participants. Pearson’s correlation between the semen parameters and blood sugar value of the study participants showed semen parameters: volume (r=-0.28, p<0.05), count (r=-0.22, p<0.05), and motility (r=-0.23, p<0.05), has a significantly week negative correlation with blood sugar level. Scatter plots also showed semen parameters: volume (r2=-0.079), count (r2=-0.048), and motility (r2=-0.053), had a significantly week negative linear correlation with blood sugar level. Conclusions: From the study it was concluded that the uncontrolled blood sugar levels affect the reproductive health of the study participants.